Cash Holding in Manufacturing Companies: A Study of Indonesia - Ardani Musa; Muhammad Arfan; Nuraini A (Journal of Accounting Research, Organization and Economics, 2020)
Objective – This study aims to examine the effect of company size, net working capital, and financial leverage on cash holding in manufacturing companies listed on the Indonesia Stock Exchange.  Design/methodology – This study is a hypothesis testing research using secondary data in the form of the financial statements of the sampled companies. Its population includes manufacturing companies listed on the Indonesia Stock Exchange for the period of 2012-2016. 87 companies were taken as samples according to predetermined criteria and 435 observations were made. To test the hypotheses, panel data regression analysis was used, where the fixed effect model (least square dummy variable-LSDV) was selected as the estimation model. Results – The results show that (1) company size has no effect on cash holding in manufacturing companies for the 2012-2016 period, and (2) net working capital and financial leverage have a negative effect on cash holding in manufacturing companies in the 2012-2016 period. The results support the existing hypothesis and theories such as trade off theory, agency theory, and pecking order theory. In addition, the results of this study can be used as a reference for investors and creditors whose net working capital and financial leverage are important factors in assessing the cash holdings of manufacturing companies in Indonesia, so that they can be used as basic guidelines in making investment decisions and financing company activities. Furthermore, the results of this study are also useful for managers of manufacturing companies in Indonesia in determining the optimal level of cash holding in which it is necessary to consider two influencing factors: net working capital and financial leverage.